Education Sector Background Note : 360° Resilience Background Paper - Bellony, Annelle; Powers, Shawn (World Bank, Washington, DC, 2021)
Natural disasters and pandemics present as external shocks to Caribbean economies and affect provision of education and learning outcomes through multiple channels. This paper analyzes resilience in the education sector to climate, disaster and health shocks in Caribbean countries through the lenses of continuity of learning during emergency situations, infrastructure and skills.